2003
DOI: 10.1046/j.1365-3091.2003.00576.x
|View full text |Cite
|
Sign up to set email alerts
|

Upward‐thickening patterns and lateral continuity of Permian sand‐rich turbidite channel fills, Laingsburg Karoo, South Africa

Abstract: Analysis of extensive exposures of the Permian Laingsburg Formation, Karoo basin, South Africa, have enabled a detailed reconstruction of the base of slope stratigraphy and palaeoenvironments in a deep‐water system characterized by a very narrow grain‐size range (fine sandstone). The deposits include an ≈ 4 km wide and 80 m thick channel complex, fringed by sandy sheet deposits that extend laterally for at least 6 km across depositional strike. Within the channel complex, individual channel fills are marked by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
53
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 58 publications
6
53
0
Order By: Relevance
“…Samuel et al, 2003;Deptuck et al, 2007;Catteral et al, 2010;De Ruig and Hubbard, 2006;Kolla et al, 2012;Jolly et al, 2016), and at outcrops (e.g. Bain and Hubbard, 2016;Grecula et al, 2003). In the Indus fan, the valley can be up to 10 km wide (Deptuck et al, 2003).…”
Section: Scale Comparison With Other Submarine Channel Systemsmentioning
confidence: 99%
“…Samuel et al, 2003;Deptuck et al, 2007;Catteral et al, 2010;De Ruig and Hubbard, 2006;Kolla et al, 2012;Jolly et al, 2016), and at outcrops (e.g. Bain and Hubbard, 2016;Grecula et al, 2003). In the Indus fan, the valley can be up to 10 km wide (Deptuck et al, 2003).…”
Section: Scale Comparison With Other Submarine Channel Systemsmentioning
confidence: 99%
“…overlying Fort Brown Formation (Figure 2) is punctuated by five sandstone-rich units (units C-G; Flint et al, 2011) that comprise slope channel-levee systems separated vertically by extensive mudstone units (Grecula et al, 2003;Figueiredo et al, 2010;Di Celma et al, 2011;Hodgson et al, 2011;Morris et al, 2014a). These mudstone units constrain the stratigraphy and have been mapped for up to 90 km (56 mi) downdip (van der Merwe et al, 2014).…”
Section: A T a S H A R E 75mentioning
confidence: 99%
“…Deep-water deposition began with distal basin floor deposits of the Vischkuil Formation (van der Merwe et al, 2009Merwe et al, , 2010, which is overlain by basin floor and base-of-slope fan systems of the Laingsburg Formation (units A and B; Grecula et al, 2003;Sixsmith et al, 2004). The muddy slope succession of the 0.5-km-thick (1640-ft-thick) …”
Section: Geologic Setting and Stratigraphymentioning
confidence: 99%
“…2 for detail). The Laingsburg Formation is further subdivided into basal Fan A, a basin-floor fan system (Sixsmith et al 2004) overlain by Units B-F. Each unit represents a period of sandstone deposition in a mud-dominated, progradational system spanning basin-floor to upper-slope environments (Grecula et al 2003). The deep-water succession has a maximum grain size of fine sandstone so -for the purpose of reservoir modelling -very-fine-grained sandstone and coarser is considered as net.…”
Section: Skeiding and Laingsburg Rubbish Dump Study Sitesmentioning
confidence: 99%
“…The deep-water succession has a maximum grain size of fine sandstone so -for the purpose of reservoir modelling -very-fine-grained sandstone and coarser is considered as net. Ongoing field-based research has shown that additional minor sandstone-prone units are present which are key to regional correlation: the A/B interfan between Fan A and Unit B and the B/C interfan between Units B and C (Grecula et al 2003), as well as a basin-wide, 30 cm thick marker bed called the Thin Siltstone Interval (TSI) within slope mudstones beneath Unit B (see Fig. 2 for detail).…”
Section: Skeiding and Laingsburg Rubbish Dump Study Sitesmentioning
confidence: 99%